1993
DOI: 10.1128/jvi.67.3.1424-1432.1993
|View full text |Cite
|
Sign up to set email alerts
|

Adult mouse kidneys become permissive to acute polyomavirus infection and reactivate persistent infections in response to cellular damage and regeneration

Abstract: Kidneys of newborn (but not adult) mice are normally highly permissive for polyomavirus (Py) infection and readily establish persistent infections. We have proposed that ongoing cellular differentiation, which occurs in newborn mice, may be necessary for a high level of in vivo Py replication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(70 citation statements)
references
References 52 publications
1
66
1
1
Order By: Relevance
“…One possibility is that coviral-induced cellular damage results in high levels of cellular division and differentiation, creating conditions permissive for HBoV replication. A similar mechanism has been shown for polyomavirus infection in mice [18]. In addition, respiratory viral infections may suppress immune system functions to make the host more susceptible to infection with HBoV.…”
Section: Characteristicsupporting
confidence: 58%
“…One possibility is that coviral-induced cellular damage results in high levels of cellular division and differentiation, creating conditions permissive for HBoV replication. A similar mechanism has been shown for polyomavirus infection in mice [18]. In addition, respiratory viral infections may suppress immune system functions to make the host more susceptible to infection with HBoV.…”
Section: Characteristicsupporting
confidence: 58%
“…Danger, as originally described by Matzinger et al, is known to augment immune responses (41). In the setting of MPyV infection, it has been reported that renal injury, either by biochemical agents or by ischemia, increased susceptibility to viral replication in the kidney (29). We thus hypothesized that IRI injury would be an important clinical variable that could potentiate PVAN.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies in nontransplant mouse models have shown that injury mediated by chemical toxins or by renal artery ligation increased the permissivity of kidneys for MPyV replication (29). This, together with the observation that the magnitude of PVAN was greatest in mice infected near the time of transplantation, suggested that ischemia/reperfusion injury (IRI) contributed to the pathology of PVAN.…”
Section: Prolonged Cold Ischemia Does Not Increase the Severity Of Pvanmentioning
confidence: 98%
“…Of the five polyoma viruses infecting humans, BK virus is associated most strongly with the development of disease following transplantation, where viral replication can lead to ureteric stenosis, tubulointerstitial nephritis (polyoma virus nephropathy) or haemorrhagic cystitis [1,20,[32][33][34]. Although BKV reactivation has been reported after most types of solid organ transplantation [35][36][37][38], the incidence is disproportionately high following renal transplantation, due possibly to local tissue damage and ischaemia-reperfusion injury inducing viral replication [39,40]. As the early diagnosis of BKV reactivation may improve outcomes and reduce complications most renal transplant units have introduced surveillance programmes, with associated protocols for immunosuppression reduction or modulation [41].…”
Section: Discussionmentioning
confidence: 99%